Changing the Quality of Interaction Between Educational Theory and Practice in STEAM-Teaching - Kamolovna, Sodikova Yulduz (International Journal on Integrated Education, 2023)
Characterizing STEAM incorporates the expressions with other STEM areas, recognizing that inventiveness and the expressions are key components of learning and a key enabler for advancement. STEAM can be characterized as a way of building understanding through craftsmanship frame engagement that successfully underpins development in all ranges, with associations between craftsmanship and STEM components